Creative Synthesis: Exploring the Process of Extraordinary Group Creativity - Harvey, Sarah (Academy of Management Review, 2014)
This article provides insight into how some groups achieve extraordinary levels of creativity by reconsidering the collective process through which new ideas develop. Previous research has been premised on a model in which idea generation stimulated by divergent input increases the variance in ideas a group generates and therefore increases the chance that one of the group's ideas will be a radical, breakthrough creative product. In contrast, I present a dialectical model in which the integration of group members' perspectives (which I label creative synthesis) is the foundation for new ideas. I propose that the process of creative synthesis improves the chance that each of a group's ideas is a breakthrough. I elaborate the process facilitators of creative synthesis and the implications of the dialectical model for understanding extraordinary group creativity. Creative synthesis provides an alternative way for groups to combine their cognitive, social, and environmental resources into extraordinary output.